Post-lacustrine evolution of a tectonically-controlled intermontane basin: Drainage network analysis of the Mercure basin, southern Italy - Gioia, Dario; Corrado, Giuseppe; Danese, Maria; Minervino Amodio, Antonio; Schiattarella, Marcello (Frontiers in Earth Science, 2023)
Topographic analysis, drainage network morphometry, river profile analysis, and spatial distribution of fluvio-lacustrine terraces have been used to reconstruct the drainage network evolution in the Mercure River basin, a large intermontane tectonic basin of the axial zone of southern Apennines. Morphotectonic evolution of the study area is mainly controlled by poly-kinematics high-angle WNW-ESE and NE-SW faults, which promoted the development of a complex landscape with relict landscapes and/or low-relief erosional surfaces that occurred in a staircase arrangement at the top of the landscapes or at higher altitudes than the basin infill. The creation of the accommodation space for the deposition of the thick basin infill was related to an important tectonic phase of block-faulting along N120°-trending normal faults, which occurred in the final part of the Lower Pleistocene. Such an evolution strongly controls the longitudinal profile forms of channels draining the northern sector of the study area, which are featured by a well-developed concave-up segment in river profiles of these channels between an upward trait with lower values of channel steepness and the trace of the master fault. River profiles in north-western and south-east sectors of the Mercure River basin exhibit clear knickpoints at altitudes comparable with those of the superimposed orders of relict landscapes related to the initial formation of the tectonic basin and the subsequent evolution of the endorheic basin, with a post-lacustrine geomorphological evolution of the drainage network that is controlled by fluvial incision occurring at rates comparable than those reconstructed by independent morphotectonic markers. The erosion of the threshold of the endorheic basin occurring during the base-level fall of the MIS 12 promoted a dramatic base-level fall of about 150 m, with corresponds to a mean incision rate of about 0.35 mm/yr. Post-lacustrine evolution of the Mercure basin strongly controls the morphometric features of the drainage network, which preserves a centripetal pattern with several planimetric anomalies such as counterflow and high-angle confluences, local-scale fluvial capture phenomena and drainage divide migrations.